Early Conversion to Prednisolone/Everolimus as an Alternative Weaning Regimen Associates With Beneficial Renal Transplant Histology and Function: The Randomized‐Controlled MECANO Trial. Issue 4 (17th October 2016) - Bemelman, F. J.; de Fijter, J. W.; Kers, J.; Meyer, C.; Peters‐Sengers, H.; de Maar, E. F.; van der Pant, K. A. M. I.; de Vries, A. P. J.; Sanders, J.‐S.; Zwinderman, A.; Idu, M. M.; Berger, S.; et al.
Abstract : In renal transplantation, use of calcineurin inhibitors (CNIs) is associated with nephrotoxicity and immunosuppression with malignancies and infections. This trial aimed to minimize CNI exposure and total immunosuppression while maintaining efficacy. We performed a randomized controlled, open‐label multicenter trial with early cyclosporine A (CsA) elimination. Patients started with basiliximab, prednisolone (P), mycophenolate sodium (MPS), and CsA. At 6 months, immunosuppression was tapered to P/CsA, P/MPS, or P/everolimus (EVL). Primary outcomes were renal fibrosis and inflammation. Secondary outcomes were estimated glomerular filtration rate (eGFR) and incidence of rejection at 24 months. The P/MPS arm was prematurely halted. The trial continued with P/CsA (N = 89) and P/EVL (N = 96). Interstitial fibrosis and inflammation were significantly decreased and the eGFR was significantly higher in the P/EVL arm. Cumulative rejection rates were 13% (P/EVL) and 19% (P/CsA), (p = 0.08). A post hoc analysis of HLA and donor‐specific antibodies at 1 year after transplantation revealed no differences. An individualized immunosuppressive strategy of early CNI elimination to dual therapy with everolimus was associated with decreased allograft fibrosis, preserved allograft function, and good efficacy, but also with more serious adverse events and discontinuation. This can be a valuable alternative regimen in patients suffering from CNI toxicity. Abstract : This randomized trial in renal transplant recipients shows that with tight monitoring of drug levels, a triple calcineurin inhibitor–containing drug maintenance regimen can be tapered to a double calcineurin‐free drug regimen, and that this regimen is associated with better renal function and less interstitial fibrosis and inflammation.